Do European Central Bank Asset Purchase Programmes Matter for the Euro-area Stock Markets and Brent Crude Market? - Lin, Yih-Bey; Chang, Fu-Min; Leung, Yu-Hin; Lin, Jui-Feng; Lee, Nicholas (International Journal of Energy Economics and Policy, 2018)
This paper examines macroeconomic impacts of European Central Bank (ECB) unconventional policy on Euro stock markets and Brent crude market respectively. We use actual and confidential asset purchase programmes (APPs) data to capture the unconventional effect and apply the vector auto-regression (VAR) model. We find that when the percentage change in ECB APPs leads stock market returns in French, England and Italy as controlling either the Germany or French stock market. Controlling both French and Germany stock markets simultaneously, we find that the percentage change in ECB APPs leads stock market returns only in Italy, suggesting that ECB APPs for the segments of European stock markets matter. Finally, we find the causality from the percentage change in APPs to crude oil returns. Similar results are obtained when controlling positive percentage change in APPs. Hence, our results shed valuable lights on conducting conventional monetary policy in times of crisis. Keywords: ECB, Asset purchase programme, Stock market, Crude market, Granger causality JEL Classifications: G15, G14, E52